2017
DOI: 10.4103/pm.pm_406_16
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Plantago major extracts and its chemical compounds on proliferation of cancer cells and cytokines production of lipopolysaccharide-activated THP-1 macrophages

Abstract: Background:Plantago major has been reported to have anticancer and anti-inflammatory properties. However, its antiproliferative and anti-inflammatory mechanisms have not been fully elucidated. Moreover, which plant parts are more suitable as starting materials has not been explored.Objectives:To investigate the antiproliferative activity of P. major extracts against MCF-7, MDA-MB-231, HeLaS3, A549, and KB cancer cell lines as well as their effects on inflammatory cytokines (tumor necrosis factor [TNF]-α, inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 30 publications
3
18
0
Order By: Relevance
“…In Romanian ethnopediatry, the plant leaves were considered to be beneficial against cough, oliguria, intestinal worms, trauma, and debility [75,86]. Modern studies provided some evidence for its wound healing [164,165], antibronchitis [166], anti-inflammatory [167,168], immunoenhancing [169], and antiparasitic potential [170]. On the contrary, one adult clinical study reported the lack of diuretic effect, which is claimed by various ethnomedical systems [171].…”
Section: Comparison Of Relative Therapeutic Versatility Of Top Medicimentioning
confidence: 99%
“…In Romanian ethnopediatry, the plant leaves were considered to be beneficial against cough, oliguria, intestinal worms, trauma, and debility [75,86]. Modern studies provided some evidence for its wound healing [164,165], antibronchitis [166], anti-inflammatory [167,168], immunoenhancing [169], and antiparasitic potential [170]. On the contrary, one adult clinical study reported the lack of diuretic effect, which is claimed by various ethnomedical systems [171].…”
Section: Comparison Of Relative Therapeutic Versatility Of Top Medicimentioning
confidence: 99%
“…However, these effects were not consistent with the collection site. Methanolic extracts obtained from wild C. tenuiflora plants of Parque Nacional Lagunas de Zempoala, containing verbascoside and aucubin [ 3 ], displayed cytotoxic activity [ 6 ], whereas extracts containing these compounds obtained from wild plants of Juchitepec did not show cytotoxic activity against the same cell lines [ 8 ], even if verbascoside and aucubin are cytotoxic by themselves [ 10 , 11 ]. Thus, it was hypothesized that pharmacological interactions could affect the pharmacological activity of C. tenuiflora .…”
Section: Introductionmentioning
confidence: 99%
“…Plantago major L. (Plantaginaceae) is a perennial herb that has contributed to the folk medicine all around the world, 1 including Indonesia with wide geographical distribution. 2 Diverse pharmacological effects have been demonstrated for P. major such as anti-inflammatory, [3][4][5][6][7] wound healing, 8 antiviral, 9,10 anticancer, 9,11 anticholinesterase, 12 and immunomodulator. 9,13 Additionally, this plant has been investigated for its antioxidant activity.…”
Section: Introductionmentioning
confidence: 99%